Le problème de l’identité sexuelle des adolescents et l’absence d’éducation sexuelle dans la société algérienne - BOUGETOUCHE, Imane; KAOUANE, Mohamed (Journal of Human Sciences, 2020)
The adolescent phase considered a crucial step in the reconstruction and pursuit of gender identity. There is an impact that occurs between the behavior, personality, and biological composition of the individual, and everything relationships between them to support its differentiation, growth and psychological maturity. The adolescent seeks compelling positives on issues related to physical and physiological change, and which relate to his/ her gender identity, through which values and attitudes, beliefs and patterns of behavior appropriate to the sex to which he belongs. Furthermore, the acquisition process suggests that the gender system consists of imposing a culture to create distinctive characteristics for each species and find this through the process of sex education that begins from the period of childhood with the psychological work permanence to ensure consistency between the character inside and outside. Entering the sexual maturity phase, the individual has acquired the necessary experiences to prove a sexual identity. While contributes to physical and psychological development. This phase of human life has accomplished when conflict increases in the climax. Here, the resolution of these conflicts will contribute to the realization of the identity of the ego uniformly.The process of psychosocial self-improvement depends on the adolescent’s relationship with his or her family and others. In this phase, the interaction is distinguished by the fluctuations and contradictions exist between the duality of adolescence to seek individual independence and its need to support and depend on one’s family; it needs the support of the family and its communication and the inappropriate education, emotional and sexual orientation affect the role of both sexes and affect the reincarnation of the individual of a biological same-sex parent, which causes a disorder of his or her sexual identity also the negative effect of this disorder extend to the whole of society. In this study, we will discuss the issue of gender identity in the absence of a sex education model and identify some negative and deviational manifestations that pose a threat to the psychological health of a child and adolescent.